Landscape genetics highlights species-specific ecological influences on gene flow in highland frog populations from northeastern Brazil - José Henrique de Andrade Lima; Marco Katzenberger; Marcelo Gehara; Pedro Ivo Simões (Ecological Processes)
Abstract Background Dispersal limitations vary among species within the same region. For some species, geographic distance is the primary constraint, while for others, environmental factors such as climate and vegetation patterns play a larger role. These landscape-driven effects are shaped by species-specific ecological traits. Despite being conceptually intuitive, landscape genetics hypotheses—such as Isolation by Distance and Isolation by Environment—remain largely underexplored in tropical regions. We conducted a comparative landscape genetics study to assess the influence of geographic and environmental landscape features on genetic differentiation in two ecologically distinct anurans species: Dendropsophus oliveirai, a diminutive treefrog that uses ponds for reproduction and larval development, and Physalaemus cuvieri, a terrestrial frog that breeds in both ponds and rain pools, depositing eggs in foam nests where embryos develop. These species co-occur in highland forest enclaves within a dry vegetation matrix across the Borborema Plateau, northeastern Brazil. Methods We sampled individuals of both species in seven highland forest enclaves to assess phylogeographic patterns and genetic variation along the steep NE-SW climatic and vegetation gradient characterizing the plateau. Additionally, we collected geographic, climatic, and vegetation data for each site. We analyzed the relationships between geographic distance, environmental variation, climatic variation, and mtDNA genetic differentiation in both species using Mantel tests and Structural Equation Modeling. Results We found lower genetic differentiation in P. cuvieri, which was primarily associated with the geographic distance among enclaves, with only weak influence of environmental variation among sampling sites. Conversely, higher genetic differentiation was detected among geographic populations of D. oliveirai, mainly driven by a combination of geographic distance, environmental heterogeneity, and past climatic variation. Conclusions The contrasting genetic structures of the two species likely result from differences in their ability to traverse dry lowland areas between mesic highland forests, with Isolation by Distance and Isolation by Environment affecting each species differently. These findings suggest that both selective and neutral mechanisms contribute to genetic variation. Our study highlights that highland forests in northeastern Brazil may harbor genetically distinct anuran populations, where gene flow is constrained not only by geographic distance but also by environmental factors, especially in diminutive species with specific reproductive needs.